β(1)- and α(6)-integrin are surface markers on mouse spermatogonial stem cells - Shinohara, Takashi (The National Academy of Sciences, 1999)
Although spermatogenesis is essential for reproduction, little is known about spermatogonial stem cells. These cells provide the basis for spermatogenesis throughout adult life by undergoing self-renewal and by providing progeny that differentiate into spermatozoa. A major impediment to our understanding of the biology of these stem cells is the inability to distinguish them from spermatogonia that are committed to differentiation. We made use of the known association of stem cells with basement membranes and our spermatogonial transplantation assay system to identify specific molecular markers on the stem cell surface. Selection of mouse testis cells with anti-β(1)- or anti-α(6)-integrin antibody, but not anti-c-kit antibody, produced cell populations with a significantly enhanced ability to colonize recipient testes and generate donor cell-derived spermatogenesis. We demonstrate spermatogonial stem cell-associated antigens by using an assay system based on biological function. Furthermore, the presence of surface integrins on spermatogonial stem cells suggests that these cells share elements of a common molecular machinery with stem cells in other tissues.